THE EFFECT OF SERVANT LEADERSHIP ON THE QUALITY OF EDUCATION THROUGH THE CHARACTERISTICS OF MILLENNIAL TEACHERS - Imaduddin, Imaduddin; Putra, Hendri; Tukiyo, Tukiyo; Wahab, Abdul; Nurulloh, Ahmat (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Leadership at this time has many methods of leadership styles including democratic, transformational, authoritarian, delegative, visionary, and servant leadership that can be applied in leading an organization. One method of leadership style is servant leadership. Human resource management in the education sector still needs to be improved to improve the quality of education. Education quality is influenced by servant leadership and millennial teacher characteristics. This study aims to determine the characteristics of millennial teachers as an intervening variable. This research was conducted at the Ma'arif NU Education Foundation Talang Pasuruan with a total sample of 104 respondents. The data used are primary data obtained directly from respondents through questionnaires and the respondents are all teachers at the Ma'arif NU Talang Education Foundation which consists of the Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah educational institutions. The test results show that servant leadership affects the quality of education, the characteristics of millennial teachers affect the quality of education, and finally, the characteristics of millennial teachers can mediate servant leadership on the quality of education.